Designing and developing an e-Portfolio for second language learners in higher education - Ngui, Wirawati Yi Xe; Wendy Hiew; Vincent Pang (2020)
This study highlights the development of e-Portfolio as a writing assessment in an advanced English language course for undergraduate students at a public university in Malaysia. The e-Portfolio was developed using an instructional design model known as ADDIE (Analyse, Design, Develop, Implement, Evaluate). A pilot test that involved 43 students was conducted in the Develop stage and qualitative data were gathered using open-ended questionnaires to determine the e-Portfolio's impact. The pilot test findings proved that the e-portfolio was functional and operating as intended. The students responded positively to the e-Portfolio features with the exception of the peer preview. The findings also revealed that a majority of the students voted for e-Portfolio to continue to be implemented in the future. The study serves as a reference for instructional designers who are keen to introduce new educational tools in the language classroom. It also established that the e-Portfolio is a promising assessment tool for second language learners in higher education.